Gender differences in takeoff techniques of non-elite Russian long jumpers - Nemtsev, O.; Nemtseva, N.; Bguashev, A.; Elipkhanov, S.; Grekalova, I. (Journal of Human Sport & Exercise, 2016)
The objective of this study was to determine gender differences in takeoff techniques of Russian male and female long jumpers. The competitive performances of twenty-six male and twenty-one female athletes were videotaped with a high-speed digital camcorder for further two-dimensional analysis. It has been found that male jumpers had significantly larger takeoff velocity including its horizontal (7.96 ± 0.44 and 7.06 ± 0.32 m/s) and vertical (3.35 ± 0.44 and 2.75 ± 0.37 m/s) components, takeoff angle (22.8 ± 2.5 and 21.3 ± 2.4°), the centre of gravity (CG) height at touchdown (0.92 ± 0.04 and 0.88 ± 0.04 m) and takeoff (1.18 ± 0.06 and 1.09 ± 0.04 m), and CG to heel distance at touchdown (0.44 ± 0.06 and 0.39 ± 0.05 m). Female long jumpers demonstrated significantly larger leg angles at touchdown (59.6 ± 2.8 and 57.7 ± 3.0° for female and male athletes respectively). The study has revealed that effective jump distance has a strong correlation with takeoff velocity and ground contact time, and a medium correlation with horizontal and vertical takeoff velocity, leg angle and CG height at takeoff for female jumpers and only one medium correlation with vertical takeoff velocity for male jumpers.